TRADISI PACU JAWI DI KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR PROVINSI SUMATERA BARAT - Meza Arianti; Bedriati Ibrahim; H. Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is (1) to know the history of the origin of the tradition of Pacu Jawi in Sungai Tarab Subdistrict Tanah Datar Regency of west Sumatera Provience (2) to know how the implementation of Pacu Jawi tradition in Sungai Tarab Subdistrict Tanah Datar Regency of west Sumatera Provience (3) to know the function of Pacu Jawi tradition for the community in Sungai Tarab Subdistrict Tanah Datar Regency of west Sumatera Provience (4) to know the values that are contained in the tradition of Pacu Jawi in Sungai Tarab Subdistrict Tanah Datar Regency of west Sumatera Provience (5)to know the shifts that occur in the tradisional of Pacu Jawi in Subdistrict Tanah Datar Regency of west Sumatera Provience. This research use descriptive method with qualitative approaches which will give complete information that can useful to science. The result of this research show that the Pacu Jawi is a tradition which had already been passed down from ancestor since hundreds of years ago that is still maintained until now. Pacu Jawi has a function and contains the values for the life of the community.Key words: Pacu Jawi, Tradition